Assessment of the potential natural ventilation on typical house in Malaysia - Ooi, Wei Jie (2015)
Natural ventilation is nowadays become significantly applied in buildings to maintain a healthy and comfortable indoor climate. The driving force for natural ventilation can be introduce by allowing the wind speed pass through flow to the building. Recently in Malaysia, issues of comfortable indoor climate are expressively discuss. Therefore this study was conducted to investigate the potential of natural ventilation in Malaysian housing system. Two typical housing design were used in this study where one with jack roof system and another without. Computational Fluid Dynamic were used in this study in order to examine the potential of natural ventilation between this two typical roof systems. From the result it was clearly shown that the house with jack roof system are shows more effective compare to the roof without opening. Result also shown that the arrangement of the opening may also affected of the performance of natural ventilation. Therefore it can be conclude the proper design in roof system may introduce the ventilation of the house.